Filling the Gap: A Comprehensive Freshwater Network to Map Microplastics across Ecological Gradients in Argentina - Alfonso, María Belén; Scordo, Facundo; Epele, Luis B.; Isobe, Atsuhiko; Akmentins, Mauricio S.; et al.; Ansoar Rodríguez, Yadira; Bertrand, Lidwina; Rimondino Guido N Tagliaferro, Marina; Yacelga Villavicencio, Naomi C. (Association for the Sciences of Limnology and Oceanography, 2024)
Year 2022, Impact factor: 4.5